Housing of A350V IQSEC2 pups at 37 °C ambient temperature prevents seizures and permits the development of social vocalizations in adulthood. (1st January 2021) - Jada, Reem; Zag, Liron; Borisov, Veronika; Levy, Nina S.; Netser, Shai; Jabarin, Renad; Wagner, Shlomo; Schragenheim-Rozales, Kinneret; Shalgi, Reut; Levy, Andrew P.
Abstract: Objectives: Mutations in the human IQSEC2 gene are associated with drug-resistant epilepsy and severe behavioral dysfunction. We have focused on understanding one human IQSEC2 missense mutation (A350V) for which we have created a corresponding A350V IQSEC2 mouse model by CRISPR which demonstrates seizures when the mice are 15–20 days old and impaired social vocalizations in adulthood. We observed that a child with the A350V mutation stops having seizures when experiencing a fever of greater than 38 °C. In this study, we first sought to determine if we could recapitulate this phenomenon in A350V 15–20 day old mice using a previously established protocol to raise body temperature to 39 °C achieved by housing the mice at 37 °C. We then sought to determine if mice in whom seizure activity had been prevented as pups would develop social vocalization activity in adulthood. Methods: 15–20 day old A350V male mice were housed either at 37 °C or 22 °C. Ultrasonic vocalizations of these mice were assessed at 8–10 weeks in response to a female stimulus. Results: Housing of 15–20 day old A350V mice at 37 °C resulted in a reduction in lethal seizures to 2% (1/41) compared to 45% (48/108) in mice housed at 22 °C, p  = 0.0001. Adult A350V mice who had been housed at 37 °C as pups displayed a significant improvement in the production of social vocalizations. Conclusion: Raising the body temperature by raising the ambient temperature might provide a means to reduce seizures associated with the A350V IQSEC2 mutation and thereby allow for an improved neurodevelopmental trajectory.